2007
DOI: 10.1074/jbc.m701962200
|View full text |Cite
|
Sign up to set email alerts
|

Murine ORAI2 Splice Variants Form Functional Ca2+ Release-activated Ca2+ (CRAC) Channels

Abstract: The stimulation of membrane receptors coupled to the phopholipase C pathway leads to activation of the Ca 2؉ release-activated Ca 2؉ (CRAC) channels. Recent evidence indicates that ORAI1 is an essential pore subunit of CRAC channels. STIM1 is additionally required for CRAC channel activation. The present study focuses on the genomic organization, tissue expression pattern, and functional properties of the murine ORAI2. Additionally, we report the cloning of the murine ORAI1, ORAI3, and STIM1. Two chromosomal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 29 publications
3
84
0
1
Order By: Relevance
“…In contrast, the BmOrai1B transcript is generated from exons 1, 2, 3, and 4 but with exons 1 and 2 giving rise to the 5Ј UTR with the start methionine in exon 3. Two mouse Orai2 variants that differ only in the length of their N termini are generated from a similar alternative splicing mechanism (43).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the BmOrai1B transcript is generated from exons 1, 2, 3, and 4 but with exons 1 and 2 giving rise to the 5Ј UTR with the start methionine in exon 3. Two mouse Orai2 variants that differ only in the length of their N termini are generated from a similar alternative splicing mechanism (43).…”
Section: Discussionmentioning
confidence: 99%
“…The three highly homologous Orai1, Orai2 and Orai3 proteins are widely expressed at the mRNA level and display similar plasma-membrane expression. 28,73 All three channels activate in a store-dependent manner when co-expressed with STIM1, while the extent of their current amplitudes is 2-3 fold smaller for Orai2 and Orai3 compared to Orai1. These reduced currents may reflect differences in their expression levels, efficiency in coupling to STIM1 and distinct single channel properties.…”
Section: Store-operated Activation Of Stim/oraimentioning
confidence: 99%
“…37 Hence, the positively charged 2-APB 74 might exert part of its stimulatory action via interaction with the Orai3 selectivity filter together with further structural requirements located within transmembrane 2 and 3 that finally result in stimulated currents with altered permeation properties. For a more detailed view on other drugs that affect STIM as well as Orai proteins, we refer to Derler et al 14 Besides these three Orai channels, further Orai2 splice variants have been identified on two chromosomal loci, 73 one containing an intronless gene and a second locus that gives rise to the splice variants Orai2 long (Orai2L) and Orai2 short (Orai2S). When co-expressed with STIM1 both Orai2S and Orai2L represent Ca 2+ selective channels.…”
Section: Store-operated Activation Of Stim/oraimentioning
confidence: 99%
“…Orai1 is strongly expressed in lymphoid organs, skeletal muscle, liver, and skin (6,7). While Orai3 is detected in similar tissues as Orai1, Orai2 is predominantly found in murine brain (8) or human kidney, lung, and spleen (9). T-cells of patients with a severe combined immunodeficiency lacked CRAC currents due to non-functional Orai1 channels, caused by a single point mutation (6,(10)(11)(12).…”
mentioning
confidence: 99%